Tatton‐Brown‐Rahman syndrome: Six individuals with novel features. Issue 4 (21st January 2020) - Balci, Tugce B.; Strong, Alana; Kalish, Jennifer M.; Zackai, Elaine; Maris, John M.; Reilly, Anne; Surrey, Lea F.; Wertheim, Gerald B.; Marcadier, Julien L.; Graham, Gail E.; Carter, Melissa T.
Abstract: Tatton‐Brown Rahman syndrome (TBRS) is an overgrowth‐intellectual disability syndrome caused by heterozygous variants in DNMT3A . Seventy‐eight individuals have been reported with a consistent phenotype of somatic overgrowth, mild to moderate intellectual disability, and similar dysmorphisms. We present six individuals with TBRS, including the youngest individual thus far reported, first individual to be diagnosed with tumor testing and two individuals with variants at the Arg882 domain, bringing the total number of reported cases to 82. Patients reported herein have additional clinical features not previously reported in TBRS. One patient had congenital diaphragmatic hernia. One patient carrying the recurrent p.Arg882His DNMT3A variant, who was previously reported as having a phenotype due to a truncating variant in the CLTC gene, developed a ganglioneuroblastoma at 18 months and T‐cell lymphoblastic lymphoma at 6 years of age. Four patients manifested symptoms suggestive of autonomic dysfunction, including central sleep apnea, postural orthostatic hypotension, and episodic vasomotor instability in the extremities. We discuss the molecular and clinical findings in our patients with TBRS in context of existing literature.